Effect of concomitant diseases on the hemostasis system in the perioperative period of non-cardiac surgery - I. S. Pryakhin; S. S. Murashko; S. A. Berns; I. N. Pasechnik (Лечащий Врач)
This study examined the effect of clinical factors and antithrombotic therapy on the blood coagulation system of patients in the perioperative period. The study included 80 patients who underwent elective noncardiac surgery. Laboratory control of hemostasis was carried out using routine tests for studying hemostasis (APTT, INR) and a global test for hemostasis (thrombodynamics test). Usage of the thrombodynamics test in this study was more sensitive compared to routine tests and made it possible to identify clinical factors associated with hypercoagulable states and «decreasing in the effectiveness» of low molecular weight heparins in the postoperative period. These factors are: age over 60 years, chronic ischemic heart disease, a history of coronary artery stenting, prior antithrombotic therapy before surgery. Hypercoagulability was found on the first day after surgery in patients with deep vein thrombosis of the lower extremities compared to other patients. The use of a thrombodynamics test a day before surgery allowed to predict an increase of intraoperative blood loss volume. Perioperative bridge therapy with low molecular weight heparins in high thrombotic risk patients was significantly associated with an increase in packed red blood cells transfusion of almost two times compared with other patients and is associated with an increased risk of hemorrhagic complications. The results of the study showed that thrombodynamics test can potentially be used further with the aim of personalizing patients’ management in the non-cardiac surgery perioperative period. It also helps to predict the occurrence of hemorrhagic and thrombotic complications.